Isolasi dan identifikasi terhadap bakteri penyebab mastitis pada sapi perah di Desa Benlutu Kecamatan Batu Putih Kabupaten Timor Tengah Selatan - Kurnia Riwu Manu; Elisabet Tangkonda; Maria Aega Gelolodo (Program Studi Kedokteran Hewan, Universitas Nusa Cendana, 2019)
Mastitis is the main problem in the dairy farm because it can lead to decline in the production of milk in the large amount. Mastitis caused by various types of microbes pathogen entering the nipple. The treatment completely difficult to implement and requires great expense so precautions can be done one is doing the early detection of mastitis. The research aim to detect mastitis subklinis in of dairy cows were maintained in the village Benlutu Kecamatan Batu Putih Kabupaten Timor Tengah Selatan and to identification bacteria cause mastitis subklinis. Sample used is milk of livestock dairy cattle as much as 12 samples of milk taken with aseptic. Furthermore do mastitis test using reagen IPB-1, from 12 sample all testes positive result mastitis subklinis. Furthemore identification bacteria cause mastitis based on the characteristic of bacteria, staining of Gram, biochemistry test, katalase test and koagulase test. From this research is known that the infection bacteria that cause mastitis subklinis Staphylococcus aureus 91,6 % (11/12) and Staphylococcus epidermidis 25 % (03/12).